Peony (Paeonia lactiflora) leaf performance of two cultivars in response to ozone exposure - Shao, Zaisheng; Jing, Liquan; Zha, Li; Lu, Xiaoyan; Huo, Wenhui; Yang, Kai; Zhang, Hengfeng (Frontiers in Plant Science, 2025)
IntroductionHigh surface ozone (O3) concentration presents a significant threat to the growth and development of plants. This research aimed to evaluate the impact of O3 on peony (Paeonia lactiflora), focusing on the physiological mechanisms involved, mainly as peony is widely grown in O3 polluted regions such as Sichuan, Jiangsu, and Shandong.MethodsTwo cultivars of peony Dafugui (DFG) and Heihaibotao (HHBT) were exposed to either non-filtered air (NF, ambient O3 concentration) or elevated O3 (NF60, NF + 60 ppb) for fifty days (April 11 to May 30) in open-top chambers. Key physiological parameters, including gas exchange, pigment levels, leaf mass per area (LMA), stomatal structure, lipid oxidation, and the antioxidant defense system, were measured across three replicate chambers.ResultsThe exposure to NF60 resulted in significant reductions in light-saturated photosynthesis rate (Asat), stomatal conductance (gs), and electron transfer rate (ETR), but no changes were observed in intercellular CO2 concentration (Ci). Increased O3 levels accelerated leaf senescence, as indicated by higher malondialdehyde (MDA) and hydrogen peroxide (H2O2) levels, along with a decline in chlorophyll content. Ozone-induced led to a reduction in LMA, but the stomatal area and density were not significantly affected. The total ascorbate (AsA) content was decreased but total antioxidant capacity (TAC), phenolics, and antioxidant enzyme activity showed an increasing trend due to O3. Statistical analysis using ANOVA revealed no significant differences in the responses of leaf indices between the two peony cultivars to O3 stress, as indicated by the absence of significant interaction effects between O3 treatment and cultivar.DiscussionThe above results indicate that under O3 stress, peony leaves exhibit chlorosis and aggravated membrane lipid peroxidation, leading to a decline in Asat and inhibited leaf growth. The findings underscore the necessity of cultivating and promoting ozone-tolerant peony cultivars in heavily O3 polluted areas to improve the production efficiency and quality of the peony.